Effect of mulching on soil moisture conservation, yield, soil properties andprofitability in apple (Malus domestica) at cold desert region inNorth-Western Himalayas - Sharma, U; Vashisth, S; Verma, S (Journal of Horticultural Sciences, 2025)
In cold desert region of lower Spiti valley in Lahaul & Spiti district of Himachal Pradesh, India, apple (Malus domestica) is grown under adverse climatic conditions like high diurnal temperature variation, negligible rainfall (<200 mm annually), high evaporation losses during summers, low water holding capacity and timely availability of scarce irrigation water. Considering the above factors, on-farm trials were conducted for three years in lower Spiti region consisting four treatments viz., T1 : famers’ practice (no mulching), T2 : mulching with black polythene, T3 : mulching with grey polythene and T4 : mulching with dry grass. Results revealed that on an average, the dry grass mulching in apple basin resulted in 33.1 per cent higher moisture content as compared to farmer’s practice where no mulch was applied. Highest apple fruit yield (30.8 t ha-1) was recorded in T4 followed by T3 (28.2 t ha-1) and T2 (27.8 t ha-1). Dry grass mulching improved the organic carbon content of soil over initial status. Among available nutrients, nitrogen content increased over initial status in polythene mulching treatments. Available phosphorus and potassium increased in all the treatments over initial status. Higher net returns and benefit to cost ratio were obtained with dry grass mulch followed by polythene mulching.